Architecture and its sculpture in viceregal Mexico - Mullen, Robert James (University of Texas Press, 1997)
"From monumental cathedrals to simple parish churches, perhaps as many as 100,000 churches and civic buildings were constructed in Mexico during the viceregal or colonial period (1535-1821). Many of these structures remain today as witnesses to the fruitful blending of Old and New World forms and styles that created an architecture of enduring vitality." "In this profusely illustrated book, Robert J. Mullen provides a much-needed overview of Mexican colonial architecture and its attendant sculpture. Writing with just the right level of detail for students and general readers, he places the architecture in its social and economic context. He shows how buildings in the larger cities remained closer to European designs, while buildings in the pueblos often included prehispanic indigenous elements."--Jacket